Authenticity and Its Discontent as Reflected on Heinrich Böll’s The Laugher - Ni Nyoman Sarmi; Kheista Sasi Kirana; Kusuma Wijaya; Rommel Utungga Pasopati (LET: Linguistics, Literature and English Teaching Journal)
People are justified to be original but it could hinder people from their freedom as stated by Jean-Paul Sartre. The Laugher is Heinrich Böll’s short story of someone whose job is to laugh in various platforms. His laughter must be heard as original but his own life is full of pessimistic conditions. Then, how may being authentic be contested through Böll’s The Laugher? Through qualitative method on cultural studies, this paper puts tensions between being authentic by Sartre and reality of Böll’s story. The laugh seems to be authentic, but it is set to trigger other laughter, yet he is not happy though he laughs every time. He is demanded to laugh, but the laugh is bad faith as supported by Sartre. Authenticity in Böll’s story shows its own discontent. In conclusion, the story shows how laughter is done in a timed set. His laugh is not freedom since his own life is full of sad conditions.